Neonatal asphyxia as an inflammatory disease: Reactive oxygen species and cytokines - Okazaki, Kaoru; Nakamura, Shinji; Koyano, Kosuke; Konishi, Yukihiko; Kondo, Masatoshi; Kusaka, Takashi (Frontiers in Pediatrics, 2023)
Neonatologists resuscitate asphyxiated neonates by every available means, including positive ventilation, oxygen therapy, and drugs. Asphyxiated neonates sometimes present symptoms that mimic those of inflammation, such as fever and edema. The main pathophysiology of the asphyxia is inflammation caused by hypoxic-ischemic reperfusion. At birth or in the perinatal period, neonates may suffer several, hypoxic insults, which can activate inflammatory cells and inflammatory mediator production leading to the release of larger quantities of reactive oxygen species (ROS). This in turn triggers the production of oxygen stress-induced high mobility group box-1 (HMGB-1), an endogenous damage-associated molecular patterns (DAMPs) protein bound to toll-like receptor (TLR) -4, which activates nuclear factor-kappa B (NF-κB), resulting in the production of excess inflammatory mediators. ROS and inflammatory mediators are produced not only in activated inflammatory cells but also in non-immune cells, such as endothelial cells. Hypothermia inhibits pro-inflammatory mediators. A combination therapy of hypothermia and medications, such as erythropoietin and melatonin, is attracting attention now. These medications have both anti-oxidant and anti-inflammatory effects. As the inflammatory response and oxidative stress play a critical role in the pathophysiology of neonatal asphyxia, these drugs may contribute to improving patient outcomes.